Internalisasi Pendidikan Pra Nikah Oleh Penghulu Agama dan Kitab Maui’zah Al Mu‘Minin - Mubin, Nur (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
The high divorce rate in Indonesia indicates that few people do not understand the concept of education in managing their households. The majority of the community has underestimated education about the household, so prospective couples who get married do not prepare it carefully; they focus more on preparing the walimatul 'urs event, which is just a mere formality. Finally, not a few of these couples have difficulty living in their household until it ends in divorce. Seeing this fact, the writer raised the theme of Internalisation Of Household Education According To The Book Of Maui'zah Al Mu'minin. The thoughts of a figure who has summarized the book of Ihya by Al Ghozali. This study concludes that: (1) Household education, according to al Qosimy, must start with choosing a good partner, exemplary, creativity and supervision. According to the author's subjective opinion, Al Qosimy's explanation is based on verses and hadiths and the atsar of friends; although it looks global, it is curative, and there are many dhoif hadiths. However, al, Qosimy's thinking is quite comprehensive and systematic. (2) A household based on the purpose of forming a household following article 1, supported by the existence of mutual complement, helping and complementing each other is the key to creating eternal happiness based on the One Godhead.